The Role of Academic leaders in Developing Social Responsibility in the University of Hafr Al Batin - Alshammari, Adel Ayed; Alshammari, Shog Turki (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to explore the contribution of academic leaders towards the development of social responsibility at the University of Hafr Al-Batin in Saudi Arabia, as perceived by the faculty members. Additionally, the study aimed to identify the obstacles that hinder this contribution and propose suggestions to enhance it. Methods: The study utilized a descriptive-analytic method and a questionnaire to collect data. The sample consisted of 274 faculty members out of a total of 819. Results: The University of Hafr Al-Batin's academic leaders have played a significant role in developing the university's social responsibility, achieving a moderate degree of success with an average of 2.92. The results also indicated that the challenges impeding the university's social responsibility advancement were significantly high, with an average of 3.50. The primary proposals for advancing social responsibility encompassed two key aspects: integrating the university's social responsibility within its organizational structure and annual plan and designating a dedicated fund to facilitate its social responsibility efforts. Conclusions: The results indicated that university leaders moderately impact the process of fostering social responsibility. The decline of this role mainly stemmed from organizational, legal, and financial factors. This result further substantiated the sample’s perspective regarding the challenges impeding the implementation of the university's social responsibility. Hence, granting universities structured financial and administrative autonomy is necessary as it enables them to fulfill their societal obligation effectively.